SOLUBILITY ENHANCEMENT OF A DRUG BY LIQUISOLID TECHNIQUE - SANTHOSH KUMAR.K; SURIA PRABHA.K; SATISH.K; SATYANARAYANA.K; RAJA HEMANTH KUMAR (International Journal of Pharma and Bio Sciences, 2010)
Liquisoild technique is a novel concept for delivery of drugs through oral route. This approach of delivering drugs is suitable mostly for lipophilic drugs and poorly or water insoluble drugs. This approach is suitable for immediate or sustain release formulations. Design and formulation of this approach is prescribed according to new mathematical model given by Spires et al. Increasing the solubility by using a non-volatile solvent which is suitable for drug, their by dissolving the drug in the non volatile solvent and this is termed as liquid medicament . Blending the liquid medicament with mixture of carrier and coating material, liquid medicament can be converted into non adhere, dry looking powder with acceptable flow properties and compression behavior using suitable excipients and tabletting by direct compression method.